Online Monitoring of Electrochemical Degradation of Paracetamol through a Biomimetic Sensor - Mariana Calora Quintino de Oliveira; Marcos Roberto de Vasconcelos Lanza; José Luis Paz Jara; Maria Del Pilar Taboada Sotomayor (International Journal of Electrochemistry)
This paper reports, for the first time, the online monitoring to the electrochemical degradation of the paracetamol using a biomimetic sensor coupled to a Flow Injection Analysis (FIA) system. The electrochemical degradation of the drug was carried out in aqueous medium using a flow-by reactor with a DSA anode. The process efficiency was monitored at real time by the biomimetic sensor constructed by modifying a glassy carbon electrode with a Nafion membrane doped with iron tetrapyridinoporphyrazine (FeTPyPz). Simultaneously, we carried out off-line analysis by liquid chromatography (HPLC) during the experiments in order to validate the proposed system. In addition, to investigate the degradation products of the paracetamol electrolysis, we used the techniques of UPLC/MS and GC/MS.